“A Constitution Similar in Principle to That of the United Kingdom”: The Preamble, Constitutional Principles, and a Sustainable Jurisprudence - Oliver, Peter (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
In recent years, unwritten constitutional principles often find their place in Canadian constitutional law via their supposed foothold in the part of the preamble to the Constitution Act, 1867 that refers to “a Constitution similar in Principle to that of the United Kingdom”. Principles such as judicial independence, democracy, federalism, constitutionalism and the rule of law, and protection of minorities have been derived from the preamble. This article looks through over a hundred years of Supreme Court of Canada case law in order to determine what that preambular phrase has meant over time. It turns out that in the years immediately after 1867, it referred to what we now call political constitutionalism. A hundred or so years later, this same passage came to be associated with legal constitutionalism, though the Court has more recently backed away from the fullest implications of that approach. This article proposes a reading of the preamble and constitutional principles that is consistent with recent Supreme Court of Canada case law and defensible given current jurisprudential trends. That reading gives due regard to the traditional meaning of the rule of law all the while acknowledging that there are genuinely hard cases (particularly prevalent at the Supreme Court level) where neither rules nor principles provide clear answers. In those circumstances, respect for the rule of law requires as much wisdom and judgement as it does application of more prosaic legal skills. This article therefore recommends what is here referred to as a “sustainable jurisprudence” that offers an essential bridge between by now orthodox Dworkinian principle-based reasoning and contextual studies more commonly found in socio-legal, feminist, and other critical literature.